2019
DOI: 10.3389/fpls.2019.01095
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CRL4 Complexes: Surveying Chromatin States and Gene Expression

Abstract: CULLIN4 (CUL4) RING ligase (CRL4) complexes contain a CUL4 scaffold protein, associated to RBX1 and to DDB1 proteins and have traditionally been associated to protein degradation events. Through DDB1, these complexes can associate with numerous DCAF proteins, which directly interact with specific targets promoting their ubiquitination and subsequent degradation by the proteasome. A characteristic feature of the majority of DCAF proteins that associate with DDB1 is the presence of the DWD motif. DWD-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 145 publications
(171 reference statements)
1
14
0
Order By: Relevance
“…Taken together, we conclude that the corepressor HOS15 regulates the dynamic balance between transcriptional gene activation and repression in plant immunity by functioning as a substrate receptor in the E3 ubiquitin ligase complex that mediates degradation of the coactivator NPR1 to prevent target gene activation in unchallenged conditions and to limit activation during SA-mediated defense signaling. In Arabidopsis, three cullin-based E3 ubiquitin ligase complexes have been best characterized, CUL1-based ubiquitin ligase complex (SCF), CUL3-based ubiquitin ligase complex (BCR/ CLR3), and CUL4-based ubiquitin ligase complex (DCX/ CRL4) (69)(70)(71). Here, we have shown that HOS15 displays protein interactions consistent with its function as a substrate receptor for an SCF E3 ubiquitin ligase complex (SI Appendix, Figs.…”
Section: Hos15 Negatively Regulates Plant Immunity Against Bacterialmentioning
confidence: 80%
“…Taken together, we conclude that the corepressor HOS15 regulates the dynamic balance between transcriptional gene activation and repression in plant immunity by functioning as a substrate receptor in the E3 ubiquitin ligase complex that mediates degradation of the coactivator NPR1 to prevent target gene activation in unchallenged conditions and to limit activation during SA-mediated defense signaling. In Arabidopsis, three cullin-based E3 ubiquitin ligase complexes have been best characterized, CUL1-based ubiquitin ligase complex (SCF), CUL3-based ubiquitin ligase complex (BCR/ CLR3), and CUL4-based ubiquitin ligase complex (DCX/ CRL4) (69)(70)(71). Here, we have shown that HOS15 displays protein interactions consistent with its function as a substrate receptor for an SCF E3 ubiquitin ligase complex (SI Appendix, Figs.…”
Section: Hos15 Negatively Regulates Plant Immunity Against Bacterialmentioning
confidence: 80%
“…Not well understood is the co-action of COP1 with DET1, another essential protein in the suppression of photomorphogenesis in darkness ( Pepper et al, 1994 ). DET1 associates with DDB1, COP10, and DDB1-ASSOCIATED 1 (DDA1) to form a COP10-DDB1-DET1-DDA1 (C3D) complex that binds CUL4 and functions as a CUL4-based E3 ligase ( Chen et al, 2006 ; Irigoyen et al, 2014 ; Fonseca and Rubio, 2019 ). Since Arabidopsis COP1 interacted with DDB1 independently of DET1, it was proposed that the CUL4-DDB1-COP1/SPA complex may be structurally distinct from the CUL4-C3D complex ( Chen et al, 2010 ; Lau and Deng, 2012 ; Irigoyen et al, 2014 ).…”
Section: Cop1/spa As a Part Of A Cul4-based E3 Ligasementioning
confidence: 99%
“…HOS15, a DDB1-CUL4 Associated factor (DCAF) protein, encodes one of 85 WD40-repeat proteins in Arabidopsis which directly interact with speci c targets by acting as a substrate receptor for its ubiquitination and subsequent degradation by the proteasome (Ali and Yun 2020;Fonseca and Rubio 2019). Zhu, et al (2008) reported the association of HOS15 with HD2C in histone modi cation in response to cold stress in Arabidopsis.…”
Section: Biological Functions Of Hd2 Family Members In Response To Enmentioning
confidence: 99%